ENDING IN R.K NARAYAN’S NOVEL : THE GUIDE (International Journal of Food and Nutritional Sciences, 2022)
By making a detailed analysis of the different aspects of some of the major novels of RK Narayan in general and The Guide in particular, we can say with a certain amount of confidence and conviction that a clear and complete understanding of the novelists’ design and his vision is solely and squarely dependant on the two conspicuous dimensions of his art: (a) The sociocultural, economic and spiritual milieu of MALGUDI which is to be seen and studied itself as HERO of almost all his novels, because it grows and develops from a vague and small village of MALGUDI. (b) The second dimension is the deliberately designed and thematically integral OPEN ENDING in his novels where the various forces of the society of MALGUDI repeatedly keep on impinging on the character and career of the central characters, so as to transform them into the most vibrant and dynamic human beings, who in turn also influence the social matrix of MALGUDI, thus in its course this reciprocal interaction also addresses the various issues and problems raised by the novelist. It also leaves quite a few issues unaddressed and unresolved completely at the mercy of the critical acumen and taste of the readers themselves to be explored and interpreted the way they like.